A Culture‐Inclusive, Socially Engaged Agenda for Creativity Research. (12th December 2017) - Glăveanu, Vlad Petre
Abstract: The 50 years anniversary of The Journal of Creative Behavior offers a festive occasion to reflect on the recent history of the field as well as look toward its future. From the standpoint of sociocultural psychology, I celebrate the growing importance of society and culture within creativity research. However, I also note an important distinction between "social inside" and "social outside" approaches. A truly culture‐inclusive field would go beyond the view of culture as "container" and explore the ways in which sociocultural contexts actively participate in creativity. At the same time, it would examine how creative action, in turn, shapes society and culture, particularly at times of growing intolerance, nationalism, and inequality. A socially engaged agenda for creativity research is timely both conceptually and practically. Taken together, these two pillars could not only advance but also fundamentally transform our field, carrying it for the next 50 years and beyond.